Noble Metal Based Alloy Nanoframes: Syntheses and Applications in Fuel Cells - Nosheen, Farhat; Anwar, Tauseef; Siddique, Ayesha; Hussain, Naveed (Frontiers in Chemistry, 2019)
Noble metal nanostructures are being used broadly as catalysts for energy conversion in fuel cells. To overcome the future energy crises, fuel cells are anticipated as clean energy sources because they can be operated at low temperature, their energy conversion is high and their carbon release is almost zero. However, an active and stable electrocatalyst is essential for the electrochemical reactions in fuel cells. Therefore, properties of the nanostructures greatly depend on the shape of the nanostructures. Individual as well as interaction properties are greatly affected by changes in the surface area of the nanostructures. By shape controlled synthesis, properties of the nanostructures could be further enhanced by increasing the surface area or active sites for electrocatalysts. Therefore, an efficient approach is needed for the fabrication of nanostructures to increase their efficiency, activity, or durability in fuel cells by reducing the usage of noble metals. Different types of hollow nanostructures until now have been prepared including nanoboxes, nanocages, nanoshells, nanoframes (NFs), etc. NFs are the hollow unique three-dimensional structure which have no walls—they only contain corners or edges so they have large surface area. In electrocatalytic reactions, the molecules involved in the reaction can easily reach the inner surface of the nanoframes, thus noble metals' utilization efficiency increases. NFs usually have high surface area, greater morphological and compositional stabilities, allowing them to withstand harsh environmental conditions. By considering the current challenges in fabrication of noble metal based alloy NFs as electrocatalysts, this review paper will highlight recent progress, design, and fabrication of noble metal alloy NFs through different strategies—mainly photocatalytic template, electrodeposition, Kirkendall effect, galvanic replacement, chemical/oxidative etching, combination of both and other methods. Then, electrochemical applications of NFs in fuel cells toward formic acid, methanol, ethanol, oxygen reduction reaction as well as bifunctional catalyst will also be highlighted. Finally, we will summarize different challenges in the fabrication of highly proficient nanocatalysts for the fuel cells with low cost, high efficiency and high durability, which are the major issues for the highly commercial use of fuel cells in the future.